(untitled) (Journal of Educational Sciences, 2024)
This article discusses the development and testing of an innovative electronic textbook for teaching biology in high school. The development of the electronic textbook was carried out in order to effectively prepare students for the final and entrance exams in the subject of "Biology". The authors of the article present hypotheses based on the assumption of a positive impact of the electronic manual on academic performance, learning efficiency, student motivation, positive perception by teachers and anxiety reduction. The conducted research includes the development of a manual using interactive elements, multimedia, visualization and a personalized learning approach. The electronic manual was tested in high school, as a result of testing, its impact on the learning process and learning outcomes of students was assessed. When conducting the study, we used the methods of pedagogical observation, pedagogical experiment, questioning of students, the methods of M.I. Rozhkova, B.N. Phillips, methods of mathematical statistics Mann-Whitney U-test, Wilcoxon T-test. The results of the study confirmed the positive impact of the innovative e-learning tool on students’ progress in biology, and confirmed the hypotheses proposed by the authors. This article offers valuable scientific and practical recommendations for the application of e-learning tools in the educational process and the enrichment of biology teaching in high schools. Key words: electronic study guide, biology, final exams, unified national testing, information and communication technologies, self-study, interactive technologies.